Pengaruh Komunikasi Interpersonal Pimpinan Terhadap Peningkatan Kinerja Karyawan PT Lipwih Synergylab Estetika Kabupaten Bekasi Provinsi Jawa Barat - Nardiand, Roro Alit; Furrie, Wulan; Irrianda, Jhulianfika; Saptamathia, Kikky Rizki (LUGAS Jurnal Komunikasi, 2024)
This study aims to determine and identify how a leader’s interpersonal communication affects the improvement of employee performance at PT Lipwih Synergylab Estetika in Bekasi Regency, West Java Province. The research population is all employees who work at the company, both permanent employees and contract employees. The sample used consisted of 38 respondents selected using a non-probability sampling technique with the type of saturated sample (saturation sampling) where the entire population was sampled. The data collection technique used was the distribution of questionnaires using a Likert Scale calculation. The analytical techniques used in this study included instrument testing (validity and reliability test), descriptive analysis, simple linear regression analysis, correlation coefficient analysis (r test), coefficient of determination analysis (R Square test), and hypothesis testing (partial effect significance test [t test]) with the help of SPSS program for mac 26.0. The results of data processing indicate that interpersonal communication of a leader affects the improvement of employee performance at PT Lipwih Synergylab Estetika in Bekasi Regency, West Java Province with an R Square value of 0.536, which means that the Leader’s Interpersonal Communication variable (X) affects the Employee Performance Improvement variable (Y) by 53.6 %, with the remaining 46.4% being the influence of other variables not examined and explained in this study.